Thaharah Sebagai Dasar Kesucian Dalam Islam: Kajian Tentang Pengertian, Macam-Macam, Dan Praktik Bersuci - Surya Bakti; Syah Nabil Ummam Ali; Intan Nikita; Wulan Ramadhani; Dini Natasya; Adinda Aulia Syahputri (Journal of Contemporary Gender and Child Studies, 2026)
This study aims to examine the concept of taharah as the foundation of purity in Islam, encompassing its definition, various types, and purification practices as derived from the Qur'an, hadith, and Islamic jurisprudence. Taharah plays a crucial role in the lives of Muslims, serving as a prerequisite for various acts of worship, particularly prayer, while also contributing to physical, spiritual, and social cleanliness. The methodology employed involved desk research using a qualitative descriptive approach. Data were obtained through a comprehensive examination of various sources, including the Qur'an, hadith, fiqh literature, scientific texts, and relevant academic journals. Content analysis techniques were used to conduct a thorough examination of the concept of taharah in Islam, with the aim of achieving a deeper understanding of its implications. The study findings indicate that taharah represents a diverse concept of purification, encompassing the removal of hadas and najis through various methods, including ablution (wudu), ritual bathing (ghusl), tayammum (cleansing of impurities), and cleansing of najis (cleansing of impurities). Thaharah is a fundamental prerequisite for the performance of acts of worship, but also has educational, health, and character-building value. Thus, understanding and practicing thaharah correctly is very important in realizing a clean, healthy life, and in accordance with the guidance of Islamic law